SELECTION OF CATTLE BY PRODUCTION TYPES - Пікула, Оксана (Modern engineering and innovative technologies, 2022)
It was established that in order to accelerate the selection of the Ukrainian Black-and-White dairy breed, it is advisable to conduct selection by production types, where for milk production enterprises preference should be given to the dairy type of cows